Pengaruh Kualitas Produk, Harga dan Brand Image Terhadap Keputusan Pembelian : (Studi Kasus Mahasiswa Jurusan Farmasi Universitas Perintis Indonesia) - Saiful Anwar; Linda Gusnita (CV. Ulil Albab Corp, 2022)
Consumer purchasing decisions are processes where consumers choose and evaluate products or services, often consumers consider various things that suit their needs in the buying decision process. This study aims to test whether product quality, price and brand image affect purchasing decisions (a case study of a student majoring in pharmacy at an Indonesian pioneer university). Sources of data used in this study is primary data. The population in this observation is students majoring in pharmacy at the pioneering Indonesian universities, totaling 532 students. The sampling technique in this research is purposive sampling. the number of samples in this study were 98 students. The analytical method used is multiple regression analysis. The conclusion of this study is that Product Quality (X1) has a positive and significant effect on purchasing decisions, Price (X2) has a positive and significant effect on purchasing decisions and Brand Image has a positive and significant effect on purchasing decisions.